The SCF/c-KIT system and imatinib actions in prostate cancer: a cross-talk with RGN? - Cardoso, Henrique José Matos Morão Mingote (2014)
The progression of prostate cancer (PCa), from an early stage confined to prostate to a more aggressive form, is associated with loss of androgen responsiveness. At this stage, PCa cells proliferate independently of androgens actions (the so-called hormone refractory prostate cancer, HRPC), which cause the failure of classical androgen ablation therapies and restricts the therapeutic options for this usually lethal form of disease. Imatinib mesylate is a chemotherapeutic drug that inhibits the tyrosine kinase activity of c-KIT receptors among others, and has been successfully used to treat leukemias and gastrointestinal stromal tumors. However, its application for treatment of PCa has not been totally effective with preclinical models and clinical experimentation producing discordant results. On the other hand, regucalcin (RGN), a calcium (Ca2+)-binding protein that regulates intracellular Ca2+ homeostasis and the activity of several proteins involved in intracellular signaling pathways, namely, kinases and phosphatases, has been associated with suppression of cell proliferation in rat prostate. These raised the question whether RGN may regulate the expression of c-KIT and its ligand, the stem cell factor (SCF). Therefore, the present dissertation firstly aimed to analyze the cytotoxic effects of imatinib in two cell line models of HRPC, DU145 and PC3 cells. Moreover, the effect of RGN on the expression of SCF/c-KIT in rat prostate was evaluated by means of a transgenic animal model overexpressing RGN (Tg-RGN). Finally, the subcellular localization of RGN in HRPC cell lines and its association with a-tubulin was investigated. DU145 and PC3 cells were incubated with 20 µM imatinib for 48 and 72 hours. The MTS assay was used to assess cell viability in response to imatinib and the colorimetric measurement of the enzymatic activity of caspase-3 was included as an end-point of apoptosis. The expression of cell-cycle and apoptosis regulators in response to imatinib, and the expression of SCF/c-KIT in Tg-RGN vs. wild-type rats were determined by real-time PCR and Western Blot. The expression of RGN in HRPC cells lines in its association with a-tubulin were evaluated through fluorescent immunocytochemistry. Treatment with imatinib decreased the viability of DU145 cells at 48 and 72 hours. Although imatinib decreased the viability of PC3 cells upon 6 hours of treatment, thereafter cell viability significantly increased in relation to control. Accordingly, the enzymatic activity of caspase-3 was increased in DU145 cells whereas diminished activity of caspase-3 was observed in PC3 cells treated with imatinib for 48 and 72 hours. Moreover, DU145 cells displayed reduced expression of anti-apoptotic protein Bcl-2 and increased levels of the executioners of apoptosis caspase-8 and caspase-9. No differences were observed on the expression levels of these apoptosis related proteins in PC3 cells. The mRNA expression of cell cycle inhibitor p21 was increased in both DU145 and PC3 cells. Also, the mRNA levels of VEGF were decreased in DU145 cells in response to Imatinib but the opposite effect was seen in PC3 cells. To start explaining the differential response of DU145 and PC3 cells to imatinib, the expression of c- KIT receptor in these cell lines was characterized. Fluorescent immunocytochemistry and Western Blot analysis showed that the expression of the active membrane-bound c-KIT is decreased in PC3 cells relatively to DU145. In addition, PC3 cells presented increased expression of truncated isoforms of c-KIT. Relatively to RGN the results obtained showed that the expression of SCF/c-KIT system is diminished in the prostate of Tg-RGN animals, which is in accordance with the antiproliferative effects of RGN, and indicates that regulation of SCF/c-KIT system may be a mechanism by which RGN restricts proliferation. Moreover, it was confirmed the expression of RGN in HRPC cells and its co-localization with a-tubulin, a fundamental component of microtubules. The results presented in this dissertation indicated that Imatinib was effective inducing apoptosis of DU145 cells likely through the inactivation of c-KIT. On the other hand, the paradoxical effects of imatinib in PC3 cells may be associated with the presence of truncated isoforms of c-KIT for which no definitive role has been established. These findings also contributed to understand the inefficacy of imatinib as therapeutic option in PCa. Moreover, the role of RGN as an antiproliferative molecule controlling cell cycle was further highlighted by the observed decreased expression of SCF/c- KIT system with overexpression of RGN, as well as, by the association of RGN with components of the cell division machinery.